Pengaruh Kualitas Pelayanan dan Produk terhadap Kepuasan Nasabah di PT Pegadaian Syariah Cabang Kuala Simpang - Nurazizah Nurazizah; Dewi Shinta W. Lubis (CIVITAS: Jurnal Studi Manajemen, 2022)
PT. Pegadaian (Persero) is one of the non-banking credit institutions that serve the public in order to get funds quickly through credit. To improve customer satisfaction, PT Pegadaian is very demanding for all branch outlets to improve service quality. This study aims to analyze the effect of service and product quality on customer satisfaction through customer trust at PT Pegadaian Syariah Kuala Simpang Branch. This study uses a quantitative method involving 133 respondents, sampling using random sampling, namely the determination of samples that provide equal opportunities for each customer population to be sampled. Data collection is done by using questionnaires. The data obtained were analyzed using statistical formulas, with multiple linear regression models namely path analysis processed with SPSS version 18 program. The results of the study showed that partially service quality had no effect on customer satisfaction, while the product had a positive and significant effect on customer satisfaction, while Simultaneously the quality of service and product has a positive effect on customer satisfaction at PT Pegadaian Syariah Kuala Simpang Branch.